2014
DOI: 10.1016/j.pedhc.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Acute Lower Respiratory Infections in Children Younger Than 5 Years: Identification and Treatment

Abstract: Vitamin D supplementation is a low-cost, low-risk intervention that providers should consider for children, especially those at high risk for ALRI. Practitioners should follow current recommendations when prescribing vitamin D supplementation for infants and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
(75 reference statements)
0
20
0
4
Order By: Relevance
“…Observational studies indicate that vitamin D3 deficiency is a predisposing factor for infections and may contribute to increased risk of lower and upper respiratory tract infections [25][26][27] . In their review, Vanherwegen et al [28] reported that, inflammation is a common factor in many chronic disorders, and concern has been raised about the impact of vitamin D3 deficiency on several inflammatory immune processes.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies indicate that vitamin D3 deficiency is a predisposing factor for infections and may contribute to increased risk of lower and upper respiratory tract infections [25][26][27] . In their review, Vanherwegen et al [28] reported that, inflammation is a common factor in many chronic disorders, and concern has been raised about the impact of vitamin D3 deficiency on several inflammatory immune processes.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia is an inflammation of the lung parenchyma and filling of alveolar air spaces with inflammatory cells caused by viruses, bacteria, or a mixture of both. The most common viral causes are influenza, parainfluenza, adenovirus, and RSV, while bacterial pneumonia is caused by group A betahemolytic streptococcus [70]. The symptoms of pneumonia are quite similar to those of bronchiolitis, with fever, cough, and difficulty in breathing, but chest radiography is needed to confirm diagnosis.…”
Section: Acute Lower Respiratory Tract Infectionsmentioning
confidence: 99%
“…The circulating 1,25D is largely derived from conversion of 25D to 1,25D by the 1‐alpha‐hydroxylase in the kidney, but the important point is that immune cells also have the 1‐alpha‐hydroxylase and can convert 25(OH)D to 1,25(OH)D directly, which results in synthesis of cathelicidin, a peptide capable of destroying infectious agents . Indeed, a recent clinical trial showed that vitamin D 3 supplementation was associated significantly with enriched immune function, transcriptional regulation, cell cycle activity, DNA replication, and response to stress, and a 2014 review found that 13 of 18 studies examined, showed that vitamin D deficiency was prevalent among children with acute respiratory infections . Also, a study performed in hospitalized children classified as with acute lower respiratory infections (ALRIs) versus non‐ALRI‐classified hospitalizations, found that 32% (24/74) children had 25OHD 3 levels <75 nmol/L compared with 47% (14/30) among children hospitalized for other reasons …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Indeed, a recent clinical trial showed that vitamin D 3 supplementation was associated significantly with enriched immune function, transcriptional regulation, cell cycle activity, DNA replication, and response to stress, 6 and a 2014 review found that 13 of 18 studies examined, showed that vitamin D deficiency was prevalent among children with acute respiratory infections. 7 Also, a study performed in hospitalized children classified as with acute lower respiratory infections (ALRIs) versus non-ALRI-classified hospitalizations, found that 32% (24/74) children had 25OHD 3 levels <75 nmol/L compared with 47% (14/30) among children hospitalized for other reasons. 8 Multiple studies have shown an association between vitamin D deficiency and respiratory [9][10][11][12][13][14][15][16] and bloodstream infections.…”
Section: Introductionmentioning
confidence: 99%